2019
DOI: 10.3389/feart.2019.00316
|View full text |Cite
|
Sign up to set email alerts
|

Mg and Li Stable Isotope Ratios of Rocks, Minerals, and Water in an Outlet Glacier of the Greenland Ice Sheet

Abstract: Magnesium and lithium stable isotope ratios (δ 26 Mg and δ 7 Li) have shown promise as tools to elucidate biogeochemical processes both at catchment scales and in deciphering global climate processes. Nevertheless, the controls on riverine Mg and Li isotope ratios are often difficult to determine as a myriad of factors can cause fractionation from bulk rock values such as secondary mineral formation and preferential weathering of isotopically distinct mineral phases. Quantifying the relative contribution from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 111 publications
(241 reference statements)
4
9
0
Order By: Relevance
“…Then, element-to-Na ratios can be used to assess the dissolution of different silicate and trace minerals and the precipitation of secondary phases (Figure 4). As noted in previous studies, the dissolved composition of the streams draining the Leverett and Russell glaciers is for the most part consistent with the dissolution of dominant gneissic bedrock minerals, such as plagioclase, K-feldspar, and hornblende, with some additional contribution of Ca from either trace carbonates or Ca-rich silicates [ Figure 4B proposed preferential leaching of glacially ground biotite in the Leverett catchment Auqué et al, 2019;Hindshaw et al, 2019). Since biotite and other micas typically exhibit higher Ge/Si ratios than other silicates (Mortlock and Froelich, 1987;Filippelli et al, 2000;Kurtz et al, 2002), their preferential weathering could result in elevated Ge/Si of the dissolved phase, as proposed previously for glacial streams in Alaska (Anders et al, 2003).…”
Section: Field Signaturessupporting
confidence: 79%
See 3 more Smart Citations
“…Then, element-to-Na ratios can be used to assess the dissolution of different silicate and trace minerals and the precipitation of secondary phases (Figure 4). As noted in previous studies, the dissolved composition of the streams draining the Leverett and Russell glaciers is for the most part consistent with the dissolution of dominant gneissic bedrock minerals, such as plagioclase, K-feldspar, and hornblende, with some additional contribution of Ca from either trace carbonates or Ca-rich silicates [ Figure 4B proposed preferential leaching of glacially ground biotite in the Leverett catchment Auqué et al, 2019;Hindshaw et al, 2019). Since biotite and other micas typically exhibit higher Ge/Si ratios than other silicates (Mortlock and Froelich, 1987;Filippelli et al, 2000;Kurtz et al, 2002), their preferential weathering could result in elevated Ge/Si of the dissolved phase, as proposed previously for glacial streams in Alaska (Anders et al, 2003).…”
Section: Field Signaturessupporting
confidence: 79%
“…The chemical composition of the AK, QK, and Watson rivers, as well as of the Isunngua streams at similar locations to those sampled here, has been previously studied in detail by a number of researchers (e.g., Wimpenny et al, 2010, Wimpenny et al, 2011Graly et al, 2014;Hindshaw et al, 2014, Hindshaw et al, 2019Yde et al, 2014;Hatton et al, 2019a). In general, the majority of weathering reactions are thought to occur in the subglacial environment, characterized by a large reactive mineral surface area due to glacial comminution and relatively short (but seasonally variable) water transit times, similar to many other glacial systems (Tranter and Wadham, 2014).…”
Section: Field Signaturesmentioning
confidence: 88%
See 2 more Smart Citations
“…Silicate weathering typically results in low δ 26 Mg values of runoff, and high δ 26 Mg values in clay minerals [21,22]. Recent studies, however, have shown that the direction of Mg fractionation during weathering can be mineral-specific [23][24][25][26][27][28]. Also soil exchange processes can be isotopeselective [29].…”
Section: Introductionmentioning
confidence: 99%